The Fundamentalist Approach of Sheikh Abd Al-Karim Al-Mudarris in His Interpretation of The Talents of The Rahman : The Study of Governance as A Model - Hawri Omar Awla; Muhammad Anwar Saber (QALAAI ZANIST JOURNAL, 2023)
The Kurdish nationalism, since God honored them with Islam, did not skimp on their service to this religion, and as it is known that it presented men whose names entered this bright history, they participated in building Islamic civilization, from the first centuries of the message, until it reached the present day. This research is a statement of the method used by Sheikh Abd al-Karim, the Kurdish teacher, in terms of issues and topics related to the science of the principles of jurisprudence - the investigations of judgment as a model - in his interpretation marked by ((the talents of the Most Merciful)). The theologians are fundamentalists, and we notice that he takes into account in his writing the style of those who preceded him from among the great and advanced commentators. So that he deals with each of them in the appropriate place for them, and in it he combined the interpretation of the Qur’an withwhat is narrated and opinion, as he was sticking in his approach to the path of the Shafi’is in judging issues, especially Abu Hamid Al-Ghazali - may God have mercy on him - And you see him adopting the doctrine of the public in making the mandated rulings five, unlike those who make it seven like the Hanafis, and he considered determination and permission from the positive rulings unlike those who prepare him from the mandated rulings, and he does not separate in transactions between corruption and invalidity, unlike the Hanafis who consider the contract to be corrupt if it loses one of its conditions and void if it is lost A corner of it. And since he is the Ash’ari school of thought in the creed, he cared in his interpretation to mention the rational issues, and went to what the Ash’aris went to in the issue of rational improvement and ugliness, so he believes that there is no intrinsic goodness in actions until God obliges Him to command them, nor intrinsic ugliness until God obliges Him to forbid them, and if The mind is not independent to comprehend the judgment of God, but rather the mediation of the messengers is necessary. Thus, you see him adhering to the doctrine of the majority of fundamentalists in most of his issues, and he notices that he does not miss an issue unless he has inferred it with the evidence he has.